2020
DOI: 10.1021/acs.jpcc.0c07800
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Dependent Growth Behavior of Atomic-Layer-Deposited Zinc Oxide and Zinc Tin Oxide Thin Films for Thin-Film Transistor Applications

Abstract: The growth behaviors and electrical performances of semiconducting ZnO, SnO2, and (Zn,Sn)­O x thin films, grown by atomic layer deposition (ALD) using O3 as the oxygen source, were studied. A significant incubation stage was observed for ZnO ALD on the Si substrate, but not for the SnO2 thin-film substrate. The incubation cycles, along with the grain size, were increased with O3 feeding time, implying that the reactivity of the Zn-precursor varied with the degree of oxidation of the Si surface. The adsorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 64 publications
2
14
0
Order By: Relevance
“…Although binary metal‐oxide channel systems offer simple composition and processing, securing the high mobility and controllability of V TH and excellent I ON/OFF ratio simultaneously can be difficult. To overcome this limit of binary oxides, multi‐component oxide materials such as ternary (indium gallium oxide [IGO], 55–57 indium zinc oxide [IZO], 58–60 and zinc tin oxide [ZTO] 61,62 ) and quaternary oxide (indium gallium zinc oxide [IGZO], 63–68 and indium zinc tin oxide [IZTO] 69,70 ) species have been examined as active‐material candidates for high‐performance TFTs. The design rationale should balance mobility enhancement and carrier suppression.…”
Section: Ald‐derived N‐channel Oxide Tftsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although binary metal‐oxide channel systems offer simple composition and processing, securing the high mobility and controllability of V TH and excellent I ON/OFF ratio simultaneously can be difficult. To overcome this limit of binary oxides, multi‐component oxide materials such as ternary (indium gallium oxide [IGO], 55–57 indium zinc oxide [IZO], 58–60 and zinc tin oxide [ZTO] 61,62 ) and quaternary oxide (indium gallium zinc oxide [IGZO], 63–68 and indium zinc tin oxide [IZTO] 69,70 ) species have been examined as active‐material candidates for high‐performance TFTs. The design rationale should balance mobility enhancement and carrier suppression.…”
Section: Ald‐derived N‐channel Oxide Tftsmentioning
confidence: 99%
“…A ternary ZTO system has the advantages of low material costs due to indium‐ and gallium‐free composition and reasonable stability compared with IGO and IZO systems. Kim et al 62 reported the impact of cation composition on the electrical characteristics of ZTO TFTs. The ALD growth mechanism of binary ZnO and SnO 2 films was compared using substrates of bare silicon and SiO 2 /Si.…”
Section: Ald‐derived N‐channel Oxide Tftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc–tin oxide (ZTO) is a wide bandgap semiconductor (Eg = ~3.6 eV) [ 1 , 2 , 3 , 4 ] that has been studied as a potential material for electronic and energy devices, such as thin-film transistors [ 5 , 6 , 7 , 8 ], versatile sensors [ 9 , 10 ], and solar cells [ 11 , 12 , 13 ]. The ZTO film has promising properties, including transparency [ 14 , 15 , 16 ], flexibility [ 14 , 15 ], and semiconducting ability [ 6 ], with high electron charge transport behavior that offers desirable electronic and energy materials.…”
Section: Introductionmentioning
confidence: 99%
“…ZTO films can be synthesized using solution- and vacuum-based processes [ 17 ]. Various synthesis approaches have been developed for ZTO films, owing to their compatibility, including sputtering [ 18 , 19 , 20 , 21 ], atomic layer deposition (ALD) [ 3 , 8 , 22 , 23 ], chemical vapor deposition (CVD) [ 24 , 25 , 26 , 27 ], spin-coating [ 28 , 29 , 30 , 31 , 32 ], and printing techniques [ 6 , 7 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%